The divergent fates of primitive hydrospheric water on Earth and Mars - Wade, Jon (2017)
Despite active transport into Earth’s mantle, water has been present on our planet’s surface for most of geological time1,2. Yet water disappeared from the Martian surface soon after its formation. Although some of the water on Mars was lost to space via photolysis following the collapse of the planet’s magnetic field3,4,5, the widespread serpentinization of Martian crust6,7 suggests that metamorphic hydration reactions played a critical part in the sequestration of the crust. Here we quantify the relative volumes of water that could be removed from each planet’s surface via the burial and metamorphism of hydrated mafic crusts, and calculate mineral transition-induced bulk-density changes at conditions of elevated pressure and temperature for each. The metamorphic mineral assemblages in relatively FeO-rich Martian lavas can hold about 25 per cent more structurally bound water than those in metamorphosed terrestrial basalts, and can retain it at greater depths within Mars. Our calculations suggest that in excess of 9 per cent by volume of the Martian mantle may contain hydrous mineral species as a consequence of surface reactions, compared to about 4 per cent by volume of Earth’s mantle. Furthermore, neither primitive nor evolved hydrated Martian crust show noticeably different bulk densities compared to their anhydrous equivalents, in contrast to hydrous mafic terrestrial crust, which transforms to denser eclogite upon dehydration. This would have allowed efficient overplating and burial of early Martian crust in a stagnant-lid tectonic regime, in which the lithosphere comprised a single tectonic plate, with only the warmer, lower crust involved in mantle convection. This provided an important sink for hydrospheric water and a mechanism for oxidizing the Martian mantle. Conversely, relatively buoyant mafic crust and hotter geothermal gradients on Earth reduced the potential for upper-mantle hydration early in its geological history, leading to water being retained close to its surface, and thus creating conditions conducive for the evolution of complex multicellular life.